Development of Learning Videos on Basic Soccer Game Techniques At The Junior High School Education Unit Level - Muhammad David; Hartati Hartati; Herri Yusfi; Iyakrus Iyakrus; Wahyu Indra Bayu (Syntax Literate, 2023)
The development of educational civilization and technology is expected to make it easier teachers in order to create and produce learning media that can be used practically and efficiently. Sports and health Physical Education subjects are one of the subjects that can utilize technology in the learning process. This research aims to determine the validity, practicality and effectiveness of tutorial video learning media. This research is development research (R&D). This research produced a learning media product that can be used in Physical Education Subjects for Junior High School Foottball material. This study was validated by 3 experts and declared suitable for use, the results of the effectiveness test in the small group of this study showed a figure of 18,330 for T count greater than T table 1.761 while the effectiveness test result in a large group was 29.215 for Tcount greater than Ttable 1.691 which means the study is effective for improving the cognitive abilities of learners. Learning through this medium can be accessed online and offline. This research shows that tutorial video physical education learning media developed and tested for validity and effectiveness can be used in teaching and learning activities.